2015
DOI: 10.21863/jshrm/2015.4.1.002
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Work Life and Job Satisfaction: A Case of Veterinary Doctors in Punjab

Abstract: The present study attempts to establish the association between Quality of Work Life (QWL) and job satisfaction among the veterinary doctors of Punjab. Multiple linear regression analysis has been employed to examine how far the factors of QWL identified with the help of factor analysis affect the job satisfaction. Job satisfaction is a dependent variable and factors, Monetary Consideration, Social Relations at Work, Constitutionalism at Work, Pride in Job, Facilitation for Current Performance and Future Growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The bad reward is also reflected in the non-significant correlation between the number of training and years of experience. Kochar (2015) found that there is a strong association between (Monetary Consideration) (Facilitation for Current Performance and Future Growth) with job satisfaction.…”
Section: Job Facilities and Job Satisfactionmentioning
confidence: 96%
“…The bad reward is also reflected in the non-significant correlation between the number of training and years of experience. Kochar (2015) found that there is a strong association between (Monetary Consideration) (Facilitation for Current Performance and Future Growth) with job satisfaction.…”
Section: Job Facilities and Job Satisfactionmentioning
confidence: 96%